PELAKSANAAN PROGRAM PESERTA KKN DALAM PENINGKATAN KEGIATAN KEAGAMAAN DI DUSUN TOWO DESA PATALAN NGAWI - Shodiqul Bahroyni; Rolisa Wulan Mutawathi'i (Institut Agama Islam Tribakti Kediri, 2022)
The problem that will be raised in the community service program through this Community Service Program is to increase various community activities in the religious and social fields. This community service program was carried out in Patalan Village, Kendal District, Ngawi Regency on January 27 to March 4, 2022 using PAR methods and a case study approach, namely by observing and describing the situation in Patalan Village more deeply. Data collection was carried out by several strategies, namely, discussions with field supervisors, in-depth interviews with village heads, hamlet heads, community leaders and religious leaders in Patalan Village which aimed to find information related to the problems that exist in Patalan Village. Discussion on solutions to overcome problems in Patalan Village. As well as the implementation of work programs as a form of implementation of solutions to problems encountered. The result of this community service program is the realization of a program to increase activities in the religious field by implementing banjari prayer programs, madin/TPA assistance, yasinan assistance, private tutoring, and GEMAS (Mosque Cleaning the Mosque).